Production of activated carbon from landscaping waste for the removal of dyes - Ahmad, Norlailiza (2015)
Landscaping waste is one of the municipal solid wastes generated in Malaysia. In this study, a technology was applied to convert the landscaping waste into activated carbon through carbonization and activation processes. The two methods of activation chosen are physical activation and chemical activation. For physical activation, the activated carbon was activated using steam and carbon dioxide; as for chemical activation, phosphoric acid was used as the chemical agent. The physical properties of the activated carbon were then determined by scanning electron microscopic (SEM). The percentage yield for the physical and chemical activation samples were 86.52% and 90.75% respectively. For the chemical analysis different dyes concentration and different dosage of activated carbon was applied to determine the maximum adsorption capacity and percentage removal of dyes. Dyes are used to represent the colour pollution in wastewater. The activated carbon produced by chemical activation process has higher adsorption capacity and percentage removal compared to physical activation activated carbon. The maximum adsorption capacity of the dye by the activated carbon was 39.96mg/g with 100% percentage dye removal.